MEMORI, TRAUMA, DAN UPAYA REKONSILIASI PERANG TELUK II DALAM NOVEL SĀ’ATU BAGDĀD KARYA SYAHAD AL-RĀWIY - Arofah, Arofah; Arif Rokhman, Muh. (Adabiyyāt: Jurnal Bahasa dan Sastra, 2020)
Sā’atu Bagdād (2016) is a novel by Syahad al-Rāwiy which captures the dark events of Gulf War II which involved Iraq, Kuwait, the United States, and the United States coalition countries that began in 1990. This novel is divided into two parts, namely the past relating to the life of the main subject during Gulf War II and the future related to post-war life. The problem in this research is how the author reconstructs the memory and trauma that causes the subject's psychological shock and how the subject makes reconciliation efforts on the memory and trauma that befell him. To study this, the analytical descriptive method and the theory of Halbwachs memory, Caruth's trauma, and working through LaCapra were used. The results of this study indicate that the incident of Gulf War II is a personal traumatic memory that becomes the collective memory of the Iraqi people. Traumatic memories are narrated in the events of bunker protection in 1991, embargo sanctions, and subsequent war. The overlapping event caused the subject to experience back trauma, such as flashbacks, war phobia, and diaspora simulations. As for reducing the memory and trauma that continues to rage, the subject does the working-through in two ways: first, efforts to distance and let go of the past through diasporic experience and synchronizing with the new world, and second, to testify by writing novels and finding the right partner.